Peer support for adult social care in prisons in England and Wales: a mixed-methods rapid evaluation - Holly Walton; Efthalia Massou; Chris Sherlaw-Johnson; Donna Gipson; Lucy Wainwright; Paula Harriott; Pei Li Ng; Stephen Riley; Stephen Morris; Naomi J Fulop (Health and Social Care Delivery Research)
Background More adults in prison need social care support. In some prisons, prisoners (‘buddies’) are trained to provide social care support for non-personal care tasks to other prisoners. These services are not mandated but have been proposed as a solution to support social care provision in prisons. Previous research explored delivery of peer support initiatives in prisons, but there has been little research evaluating the effectiveness, implementation and experience of social care peer support. There is a need to establish how best to measure the impact and cost of peer support schemes for social care in prisons in England and Wales. Objective To evaluate peer support schemes for adult social care in prisons in England and Wales (including implementation, experiences, risks and benefits, outcomes and costs, available data, and how to measure impact and cost). Methods A rapid mixed-methods study, including a rapid systematic scoping review (n = 70 papers), a documentary analysis of 102 His Majesty’s Inspectorate of Prisons reports, and a multisite study of implementation and experience. The multisite study included 1 workshop with national and local stakeholders (n = 13) and 71 interviews with national and local leads (n = 7), prison leads from 18 prisons (n = 20), staff (n = 7), peers (n = 18) and recipients (n = 19) from 5 prisons. Qualitative analysis took place in two phases: (1) rapid analysis (using rapid assessment procedure sheets) and (2) in-depth thematic analysis. We analysed availability of data to measure impact and cost of services. Results ‘Buddies’ are frequently used in prisons in England and Wales, filling an important gap in social care provision. Implementation varies, due to service, prison, staff and prisoner factors. Prison service instruction guidelines for peer-supported social care are not consistently being implemented. This study identified areas for improvement, for example the need for formal training for buddies and staff, and the need for clear standardised employment procedures. Buddy schemes are valued by staff, buddies and recipients. Some barriers were identified, for example, lack of peer and staff training and supervision, and prison regime. Peer-supported social care may have wide-reaching benefits, yet there are several risks for recipients and buddies that must be mitigated, including the potential for exploitation of the role by staff, buddies and recipients. It is currently not possible to evaluate impact and cost due to limited data. We have developed an evaluation guide which outlines operational, cost and outcome data that needs to be collected to enable regular monitoring and/or evaluation in future. Limitations There is a lack of data collected on impact and cost, so we were unable to measure effectiveness and cost in this study. Instead, we developed an evaluation framework to inform future impact and cost evaluations. Future work National standards for peer-supported social care (including national data infrastructure) would enable robust monitoring and evaluations of effectiveness and cost-effectiveness of peer support for social care. Conclusions Peer support services are well received by different stakeholders, but standardisation is needed to ensure they are sufficiently resourced and appropriately monitored and evaluated to mitigate against risks. Study registration This study is registered as researchregistry8783. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR135689) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 1. See the NIHR Funding and Awards website for further award information. Plain language summary The problem Many adult prisoners need social care support (help with daily tasks). Some prisoners (called ‘buddies’) help others with tasks, such as cleaning their cells and collecting meals. No research has looked into this, meaning that we do not know what different people think of peer-supported social care, how it works and how to measure it. We looked at We looked at social care peer support in prisons in England and Wales, including: What support is provided. How peer support services are used. How people feel about these services. How we could measure impact and cost of these services. What we did We looked at existing evidence (e.g. social care information provided in prison inspectorate reports and publications on peer support in prisons). We spoke with 20 people in charge of these services in 18 prisons, 7 staff members, 18 ‘buddies’ and 19 prisoners who get help in 5 prisons. We held 7 interviews and a workshop with 13 people from different organisations (such as His Majesty’s Prison and Probation Service, local charities). What we found Many prisons have ‘buddies’ who help with non-personal social care tasks (such as cleaning cells). Services vary in different prisons (e.g. due to the type of prison, and partnerships between local authorities and prisons). Staff, buddies and recipients liked and valued peer-supported social care, but identified issues, such as a lack of training for peers and staff. Peer support has benefits, such as saving staff time, skills for buddies and promoting independence for those receiving support. There are risks for recipients and buddies (e.g. bullying, burden and risks of being exploited). There are not enough data to tell whether services work or save money. We suggest what data need to be collected to evaluate services in future. Conclusion These services are well received, but to overcome challenges we need: National guidelines on how they should be used. Regular monitoring. Scientific summary Background and rationale The number of those in prison requiring social care support has increased in recent years due to factors such as longer sentences, an ageing prison population, and an increased reporting of historic offences. This has led to many adults in prison needing social care support (personal and practical care and support) for a range of conditions. The Care Act in 2014 provided clarity regarding local authority and prison responsibilities for the assessment and provision of social care (e.g. personal care tasks such as help with dressing and showering). In some prisons, prisoners are providing social care support for non-personal care tasks to other prisoners (called ‘buddies’). While these services are not mandated nationally, they have been proposed as a recommended solution to support social care provision in prisons. Previous research has explored the delivery of wider peer support initiatives in prisons, but there has been little research to date evaluating the effectiveness, implementation and stakeholder experience of peer support schemes for social care. In addition to this, there is a need to establish how best to measure the impact and cost of peer support schemes for social care in prisons in England and Wales. This study sought to fill these gaps and evaluate peer support schemes for adult social care in prisons in England and Wales, looking at the following questions: What evidence on peer support schemes in prisons in general (including health, social care and educational needs) exists internationally (in relation to impact, cost, implementation and experience), what outcomes have been explored, and what data have been used? What social care is provided in adult prisons in England and Wales, and to what extent are peer support schemes for social care used in prisons in England and Wales? How are peer support schemes for social care implemented in adult prisons in England and Wales? What factors influence implementation? What are the experiences of those delivering and/or receiving peer-supported social care in adult prisons in England and Wales? What are the risks and benefits? Do experiences differ across different models of peer support? What are the outcomes and costs of peer-supported social care? What data are available to measure impact and cost? How could impact and cost of peer support schemes for social care in prisons in England and Wales be evaluated in future? Methods A rapid mixed-methods study, comprising of a rapid systematic scoping review, a documentary analysis of His Majesty’s Inspectorate of Prisons (HMIP) reports, a multisite study of implementation and experience (staff, peers and recipients), using interviews with national and local leads, prison leads (18 prisons), staff, peers and recipients (5 prisons), a workshop and a cost survey. Rapid assessment procedures were used to conduct rapid analysis of qualitative data. Following this rapid analysis, a combination of inductive and deductive thematic analysis was used to conduct an in-depth analysis of findings. This evaluation analysed what data are available to measure impact and cost; however, it was unable to explore effectiveness and cost-effectiveness of peer support schemes. Therefore, these findings relate to implementation and what should be considered in situations where peer support services for social care are used or implemented in future. Results Sites and participants Twenty prisons were selected to take part in the study, and 18 prisons participated. We conducted interviews with 7 national and local leads, 20 prison leads across the 18 prisons, and 7 staff, 18 peers and 19 recipients in the 5 case study sites. We held a workshop with 13 national and local stakeholders. Social care provision The documentary analysis of 102 HMIP reports outlined that social care provision varies in England and Wales and that some aspects of social care are more frequently reported (e.g. assessments of referrals) and others less frequently reported (e.g. care plans and reviews). There are gaps between the need for social care and provision of social care. There is a lack of consistency of reporting across HMIP reports. Interview findings also highlighted it is difficult to estimate the number of people with social care needs in prisons in England and Wales due to no nationally collected data. Certainly, numbers varied across different types of prisons and a wide range of groups of individuals require social care support. Different models of social care were used but most involved a partnership between local authority and prison and different providers are involved at different stages of the social care pathway. A range of factors influence the delivery of social care in prisons in England and Wales, including (1) dedicated social care roles, (2) collaboration between prisons and local authorities, (3) having clear processes and procedures for social care, and (4) availability of resources. These factors contextualise the implementation and factors influencing implementation of peer support schemes for social care. Peer support in prisons more generally The review of 70 studies of peer support in prisons highlighted that a variety of peer support programmes are used in prisons internationally to support a range of health, social care and educational needs. Some positive effects of peer support (e.g. in relation to disease detection, mental health, pre- and post-release behaviour, and improved knowledge and skills) were identified, but limitations in the quality of data were evident. No studies measured cost-effectiveness. Individual level factors, service level factors, and organisational factors influenced implementation of peer support schemes. The review identified a range of benefits and risks associated with peer support (e.g. burden and confidentiality). Different methods were used to measure effectiveness (e.g. surveys and cohort studies), implementation and experience (e.g. interviews, surveys and observation). Peer-supported social care The documentary analysis revealed that peer support services for social care are frequently used (40% of 102 reports), ranging from formal to informal unsupervised schemes. Interview findings demonstrated that peer support services for social care have been developed and implemented in prisons in England and Wales to formalise the otherwise informal support provided by prisoners and in response to the Care Act (2014) and perceived rising social care needs. Most prisons implemented formal peer support schemes, although some informal schemes were also identified. Implementation varied, as did leadership models and governance processes. Findings indicated that implementation of peer support may not consistently follow guidance recommended in the prison service instructions (PSIs). There were some examples of good practice identified, but none of the prisons had clear processes in place for buddies in respect of all aspects of employment and training, and some prisons had no formal training for buddies. Additionally, buddies do not always receive the training on offer. Staff, buddies and recipients reported positive views of peer support schemes demonstrating their value in prisons in England and Wales. Buddies and recipients generally felt safe, but did highlight some risks. In the site without formal peer support, recipients still highlighted social care needs being supported by informal buddies. Many factors help and get in the way of delivering and receiving peer-supported social care, including respect, reward and recognition, skills, training and awareness for staff and buddies, access and regime, time and capacity for staff and buddies, attitudes of staff and prisoners, and processes and procedures. Key attributes of peer supporters for social care were identified. Benefits and risks Peer support services for social care have a range of benefits for the wider society, prison, staff, buddies and recipients. However, several risks were identified that need to be mitigated against. The most frequently reported risks include risks to recipients (e.g. safeguarding concerns or issues, risks of bullying, accusations of stealing, buddies overstepping boundaries, and dishonesty), risks to buddies (e.g. burden and emotional risks) and exploitation of role by staff, buddies and recipients (e.g. facilitating trafficking of contraband or being asked to do things not part of the role). Factors influencing implementation Implementing peer-supported social care is influenced by a range of factors, including service factors (e.g. resources and collaboration between organisations), prison factors (e.g. prison regime and turnover of buddies), staff factors (e.g. attitudes and awareness) prisoner factors (e.g. role desirability, need and attitudes). Impact and cost measurement Workshop findings indicated that no routine national data are collected on peer-supported social care in prisons. Some local data are collected (e.g. by local authorities), but this is not widespread and data collected are often operational. There is a lack of data with which to measure benefits and risks. Additionally, data gaps affect the ability to measure impact on prisoners, staff and prisons. Cost data collected locally by prisons are limited and infrequently collected. Therefore, calculating the cost per prisoner receiving peer support and cost of the service more generally is not possible or feasible due to the availability and quality of the data. Towards monitoring and evaluating peer-supported social care Together, findings indicated that to evaluate peer-supported social care in future there needs to be some national standards developed. These national standards should include guidance on the data needed to enable monitoring of these national standards, and therefore evaluation of effectiveness, cost-effectiveness, implementation and experience. We have developed an evaluation guide that outlines operational, cost and outcome data that need to be collected to enable regular monitoring and/or evaluation in future. Limitations The study included a large sample of prisons, but we were able to include only a sample of staff, buddies, recipients, and national and local stakeholders within each. Additionally, the sample was more representative of older adults and may not represent all types of social care need. Therefore, these findings are not representative of all prisons and all staff, buddies and recipients. Additionally, there is a lack of data collected on the impact and cost of peer-supported social care schemes in prisons in England and Wales. This is, in part, because there is no formal monitoring and evaluation of their effectiveness, lack of agreement as to what a good peer support programme should look like, and the non-standardisation of the buddies’ payments. As a result of these limitations, we were unable to measure effectiveness and thorough costs in this study. Instead, we developed an evaluation framework to inform future impact and cost evaluations. Conclusions Peer support services for social care are widely used in prisons in England and Wales. Implementation of these schemes varies due to a range of service, prison, staff, and prisoner factors. There were some examples of good practice identified, but none of the prisons had clear processes in place for buddies for all aspects of employment and training (buddies and staff), and some prisons had no formal training for buddies. Additionally, buddies do not always receive the training on offer. Staff, buddies and recipients value peer-supported social care, however there were some challenges that need to be overcome to facilitate the delivery and receipt of social care peer support, for example a need to ensure that peers are recognised for their role and that peers and staff are adequately trained. Peer-supported social care may have wide-reaching benefits, yet there are a number of risks that must be mitigated. It is currently not possible to evaluate impact and cost of peer-supported social care due to limited data. The findings from this study outline implications that should be considered if peer-supported social care services are to be implemented in prisons in England and Wales. For example, national standards need to be developed for peer-supported social care programmes. These should also include guidance on the data prisons need to collect to enable monitoring of these standards, and therefore evaluation of effectiveness, cost-effectiveness, implementation and experience. To monitor and evaluate peer support schemes for social care, we have proposed an evaluation framework. Implications for managing risk, improving implementation, and improving delivery and receipt of peer-supported social care are also outlined. The development of national standards for peer support services for social care (which includes the development of a national data infrastructure) would enable future research to conduct a robust evaluation of effectiveness and cost-effectiveness of peer-supported social care, and monitor against national standards. This would enable further analyses regarding optimal service design and impact on inequalities. Study registration This study is registered as researchregistry8783. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR135689) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 1. See the NIHR Funding and Awards website for further award information.